UNDERSTANDING BEHAVIORAL ECONOMICS IN FINANCE: THE IMPACT OF HUMAN BIASES ON ECONOMIC DECISION-MAKING - Samuel Harris (Ecominds Press, 2025)
This paper explores the role of human behavior in economic decision-making, specifically in the context of behavioral economics and finance. Traditional economic models often assume that individuals act rationally, making decisions based solely on logic and maximizing utility. However, behavioral economics presents an alternative view, where economic decisions are heavily influenced by cognitive biases, emotions, and social factors. This study reviews key concepts in behavioral economics, focusing on how biases like loss aversion, overconfidence, and herd behavior can explain anomalies in financial markets. Through a comprehensive literature review and empirical analysis, this paper demonstrates the significant role of psychology in shaping economic outcomes. The findings suggest that incorporating behavioral insights into financial models can provide a more accurate understanding of market dynamics and improve decision-making processes in both individual and institutional contexts.
Keywords: Behavioral Economics, Cognitive Bias, Financial Decision-Making, Behavioral Finance, Loss Aversion, Overconfidence, Herd Behavior, Economic Decision-Making, Financial Markets, Psychological Factors.